2011
DOI: 10.1002/hipo.20821
|View full text |Cite
|
Sign up to set email alerts
|

Minimal driving of hippocampal theta by the supramammillary nucleus during water maze learning

Abstract: Previous studies have shown only modest effects of supramammillary nucleus (SuM) dysfunction on theta frequency and learning in the water maze (WM), with larger effects in other tasks. However, theta recorded from SuM, and used to trigger the production of theta-like oscillations in the hippocampus, produced reversal of the deficit in WM learning produced by theta blocking. We explored this apparent inconsistency by analyzing the relationship between SuM and hippocampal theta in the control group of this theta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…The changes in RP coherence in CTR rats could reflect increased communication between the MS and hippocampus possibly related to consolidation of spatial information and recovery of the same. In accordance, it was reported that hippocampus weakly conduced SUMn activity during the initial training, in a 1-day test of spatial learning (16 trials), whereas during the last trials of training the direction of the influence inverted so that the SUMn directed the hippocampal activity, which was also associated with an increase in coherence between the two regions during the last training trials, when the consolidation of information takes place (Ruan et al, 2011 ). Differences in the training paradigm could account for this because in the present work, 4 daily trials were given to the rats and more gradual process of consolidation could be occurring in comparison with the collapsed training (16 trials) in 1 day.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The changes in RP coherence in CTR rats could reflect increased communication between the MS and hippocampus possibly related to consolidation of spatial information and recovery of the same. In accordance, it was reported that hippocampus weakly conduced SUMn activity during the initial training, in a 1-day test of spatial learning (16 trials), whereas during the last trials of training the direction of the influence inverted so that the SUMn directed the hippocampal activity, which was also associated with an increase in coherence between the two regions during the last training trials, when the consolidation of information takes place (Ruan et al, 2011 ). Differences in the training paradigm could account for this because in the present work, 4 daily trials were given to the rats and more gradual process of consolidation could be occurring in comparison with the collapsed training (16 trials) in 1 day.…”
Section: Discussionsupporting
confidence: 71%
“…Hippocampal theta activity has been related to processing of spatial information in different behavioral paradigms in various animal species (Ammassari-Teule et al, 1991 ; McNaughton et al, 2006 ) as well as in human beings (Klimesch et al, 1994 ; Klimesch, 1999 ; Caplan et al, 2001 ; Ekstrom et al, 2005 ; Lega et al, 2014 ). The relation of theta activity and place learning has been also studied; changes in power and/or frequency of the hippocampal theta activity have been associated with efficient learning during place learning tests in the Morris maze (Pan and McNaughton, 1997 ; Olvera-Cortes et al, 2002 , 2004 ; Olvera-Cortés et al, 2012 ; Buzsaki, 2005 ; Ruan et al, 2011 ), conditioning (Berry and Seager, 2001 ; Berry and Hoffmann, 2011 ), working memory (Mitchell et al, 1982 ), and novelty detection (Aggleton and Brown, 1999 ; Vinogradova, 2001 ), among others. Moreover, deficient spatial memory has been observed after the reductions in the frequency of hippocampal theta activity (Winson, 1978 ; Pan and McNaughton, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, several studies have suggested a local generation of the theta rhythm (Lee et al, 1994; Kocsis et al, 1999), septal generation (Mizumori et al, 1989; King et al, 1998; Yoder and Pang, 2005), as well as minor contributions from additional brain structures such as the supramammilary bodies (Ruan et al, 2010). This strong phasic input impacts the firing properties of DG granule cells in several ways.…”
Section: Introductionmentioning
confidence: 99%
“…Data from 100 Sprague-Dawley rats from various previous experiments, including some reported previously (McNaughton et al, 2006 ; Ruan et al, 2011 ) were pooled for analysis. The final number of rats included in different analyses varied according to Sum/MM recording electrode placement and available behavioral data.…”
Section: Methodsmentioning
confidence: 99%
“…The understanding of information processing and function in the SuM/MM area is an incomplete mosaic. Most SuM/MM recording studies are carried out under anesthesia with only a few examining their functional significance in freely behaving animals (Sharp and Turner-Williams, 2005 ; McNaughton et al, 2006 ; Ruan et al, 2011 ; Hernández-Pérez et al, 2015 ; Gutiérrez-Guzmán et al, 2017 ). Given that single-cell and LFP theta oscillations are prominent in the HPC, SuM and MM, and that theta oscillations may reflect functional binding of circuits, we sought to characterize HPC-SuM/MM interactions at theta frequencies.…”
Section: Introductionmentioning
confidence: 99%